Зміст договору між батьками про сплату аліментів на дитину - Д’ячкова, Н. А.; Diachkova, N. A. (Право і безпека. - 2013. - № 2 (49). - С. 172-176, 2013)
Розглянуто окремі питання щодо змісту договору між батьками про сплату аліментів на утримання їхніх дітей. Зокрема, досліджено проблеми визначення розміру, способу, форми та порядку індексації аліментних виплат за договором, строку його дії та можливість визначення проміжних строків виконання обов’язків за договором тощо. Визначено шляхи усунення правових колізій, що виникають під час з’ясування питань щодо співвідношення сімейно-правової відповідальності за договором про надання утримання на дитину та відповідних цивільно-правових норм.

Family code of Ukraine grants parents wide opportunities to choose by themselves the way and order of giving allowance to their children. For example, with the help of entering into child support agreement parents can determine their rights and obligations concerning support of their children. This agreement inherently pointed at voluntary discharging of one of the parents’ alimony duties and such an agreement is family-legal, cause legal effects, which is provided in family code norms arise due to the results of its contracting and executing. Questions of alimony extend determination, which are paid according to the agreement, ways and terms of its payment and also forms of payment (payment in cash or cashless) are researched in the article. The consideration, that not only money or other material benefits as a child support, but also other legal things, for example granting the child a right to live in an apartment, which belongs to the parent – alimony payer can be conveyed to the child is backed up. Problems that appear while alimony payment place and terms determination are observed. Thus, in case of child being in children’s health camp, educational or other institution the alimony could be paid not directly to the parent – alimony receiver, but also can be transferred on institution’s account, where the child is situated. In addition, parents could provide for one-time alimony pay in the agreement, for example, when alimony payer move out to another country for constant place of abode. In case of terms of agreement violation party at fault is obliged to respond according to the agreement. In addition, the author supports consideration that in case of such terms absence in the agreement, correspond norms of civil law subject to secure of priority protection of rights and interests of minority and disable person of family could be applied. The consideration concerning impossibility of only real sustained loss vindication when the agreement is violated is disputed by the author.

Рассмотрены отдельные вопросы содержания договора между родителями о выплате алиментов на содержание их детей. В частности, рассмотрены проблемы определения размера, способа, формы и порядка индексации алиментных платежей по договору, срока его действия и возможности определения промежуточных сроков исполнения обязанностей по договору и т. д. Определены пути устранения правовых коллизий, возникающих при решении вопросов соотношения семейно-правовой ответственности по договору о выплате алиментов на ребёнка и соответствующих гражданско-правовых норм.
Content of child support agreement between parents
Содержание договора между родителями об уплате алиментов на ребёнка
Keywords: дитина; договір між батьками про сплату аліментів на дитину; утримання; відповідальність; неустойка; збитки; child; child support agreement between parents; content; responsibility; penalty; losses; ребёнок; договор между родителями о выплате алиментов на ребенка; содержание; ответственность; убытки